Factors Affecting Performance in Clinical Practice among Preservice Diploma Nursing Students in Northern Tanzania. (3rd March 2019) - Gemuhay, Helena Marco; Kalolo, Albino; Mirisho, Robert; Chipwaza, Beatrice; Nyangena, Elijah
Abstract : There is an increased call for improving the environment in which nursing students learn the clinical skills. Clinical practice in the clinical placement sites should allow students to apply their theoretical knowledge in a real environment, develop nursing skills and clinical reasoning, and observe and adapt the professional role. This study aimed at identifying the factors influencing performance in clinical practice among preservice diploma nursing students in Northern Tanzania. This study relied on a cross-sectional analysis of data collected from nursing schools in Northern Tanzania in which 208 (123 nursing students and 85 nurse tutors) participants were recruited in the study. Data was gathered using a self-administered questionnaire which collected information on sociodemographic characteristics and factors influencing clinical practice categorized in students' factors, hospital based factors, social-economic factors, and nurse tutors opinions assessed. Descriptive analyses and chi-square test were employed to understand the background information of the sample and association between variables. Majority of the nursing students (84.4%) agreed that clinical placement offers students adequate opportunity for clinical practical learning. Barriers to effective clinical learning was reported by 70.1% of the participants and the barriers include student factors such as lack of self-confidence and absenteeism, school factors such as improper supervision, and poor preparation of clinical instructors or clinical facility factors. We found a significant association between type of barrier and gender (chi-square 0.786, p=0.020) . More male nursing students (62.1%) significantly reported unsupportive environment as a barrier and anxiety was more common in female nursing students (48.9%) (p=0.020). Reporting of barriers to effective clinical learning by students from different schools of nursing was not significant (P=0.696). In addition, age of participants did not have significant association with effective clinical practice (p= 0.606). Student's factors and placement based factors played an important role to influence clinical learning experiences. Offering preclinical orientation, distributing and clarifying clinical learning objectives to students, and frequent visits and supervision of students in clinical area may improve student learning experience in clinical placement. In addition, tailoring the interventions to gender may improve learning experiences.